Smart Trash with Web Integrated Volume Monitoring and Sorting System via MQTT Protocol - Maya Rahayu; Muhammad Nurkholis Widlan; Ashari Ashari; Hutama Arif Bramantyo (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2022)
The increasing human population makes each year its production increases significantly. People's ignorance to separate the types of waste has triggered various disasters. Many studies have aimed at tackling this problem, such as smart trash bins that can sort various types of organic and inorganic materials and detect waste. However, intelligent trash can products with many functions are not all integrated into one product. In this research, a product has been created that can integrate various smart trash functions with a volume monitoring system and sorting metal, non-metal, and organic waste types monitored via the web using the MQTT Protocol. This research prototype consists of several devices, namely smart trash equipped with proximity sensors, capacitive proximity sensors, and infrared sensors. In addition, this intelligent trash is equipped with an ultrasonic sensor to detect the height of the trash. The Wi-Fi module integrated this system with web applications and the MQTT protocol. Based on the test, the system has been running well since the sensor data collection test is 70%, the delay test from the sensor input to the actuator is 3.48 s, the ultrasonic sensor reading accuracy is 97.16%, and the throughput on the monitoring website is 5084.75 bytes/sec.The increasing human population makes each year its production increases significantly. People's ignorance to separate the types of waste has triggered various disasters. Many studies have aimed at tackling this problem, such as smart trash bins that can sort various types of organic and inorganic materials and detect waste. However, intelligent trash can products with many functions are not all integrated into one product. In this research, a product has been created that can integrate various smart trash functions with a volume monitoring system and sorting metal, non-metal, and organic waste types monitored via the web using the MQTT Protocol. This research prototype consists of several devices, namely smart trash equipped with proximity sensors, capacitive proximity sensors, and infrared sensors. In addition, this intelligent trash is equipped with an ultrasonic sensor to detect the height of the trash. The Wi-Fi module integrated this system with web applications and the MQTT protocol. Based on the test, the system has been running well since the sensor data collection test is 70%, the delay test from the sensor input to the actuator is 3.48 s, the ultrasonic sensor reading accuracy is 97.16%, and the throughput on the monitoring website is 5084.75 bytes/sec.